Hemoglobin S/hemoglobin City of Hope compound heterozygote with a SubSaharan genetic background and severe bone marrow hypoplasia. - Paradisi, Irene; González, Neida; Hernández, Alba; Arias, Sergio (Investigación Clínica, 2013)
Â Hemoglobin City of Hope (Hb CH) (HBB: c.208G>A, beta 69 (E13)Gly>Ser) is a rare, anomalous change. Seven independent carriers reported so far, had not displayed any hematological manifestations. The ethnic origin of the known instances is presumably heterogeneous, although they are mainly Mediterraneans or equatorial West Africans. We describe the case of a compound heterozygote in trans for Hb S (Glu6Val) and Hb City of Hope (Gly69Ser) in an anemic two year-old boy with a severe immune-deficient phenotype and fatal chronic parvovirus B19 infection. Haplotype with the Hb S was Bantu; while it was a mixed atypical Benin/Cameroon for Hb CH. Remote ancestral origin of the City of Hope mutation in this family seems to be SubSaharan African. The compound heterozygosis in trans for hemoglobins S and City of Hope, jointly with an unfavorable HBB control region background and a viral chronic infection, seemed the cause of the fatal outcome in the patient. When accompanied by other Hb deleterious mutations in trans, Hb CH should not be considered any longer as an innocuous or functionally silent variant.